APPLICATION OF VALIDATED RP-HPLC METHOD FOR SIMULTANEOUS DETERMINATION OF METAXALONE AND DICLOFENAC POTASSIUM IN PLASMA - RAMESH, DEVI; HABIBUDDIN, MOHAMMAD (International Journal of Current Pharmaceutical Research, 2024)
Objective: The present investigation demonstrates a simple, sensitive and accurate high-pressure liquid chromatographic (HPLC) method for simultaneous determination of metaxalone (MTX) and Diclofenac potassium (DIC) in plasma by using Valsartan (VSN) as internal standard. Methods: The chromatographic separation was achieved within 10 min by using methanol: potassium dihydrogen phosphate buffer pH 4.5 adjusted with orthophosphoric acid (60:40) as mobile phase on Altima Grace Smart C-18 column (5μ; 250×4.6 mm) at flow rate of 1.0 ml/min with injection volume 25µl. The drug was extracted from plasma by liquid-liquid extraction using methanol as a solvent. The retention times of drugs (MTX and DIC) and internal standard were found to be 5.83, 9.65 and 11.79 min, respectively. This method was validated as per United States Food and Drug Administration (US-FDA) guidelines. Results: The results of the validation parameters were found to be within the acceptance limits. The method was linear in the concentration range from 25-1000 ng/ml (r2= 0.9998) and the extraction recovery was found to be 77.06% for MTX and 78.37% for DIC. The lower limit of quantification was found to be 25ng/ml and the stability of recovered samples at different conditions were found to be more than 95% for both the drugs. Conclusion: The developed method possesses good selectivity specificity, there was no interference found in the plasma blanks at retention times of MTX and DIC. We found good correlation between the peak area and concentration of the drug under prescribed conditions. Furthermore, the method can also be used to estimate the pharmacokinetic parameters of MTX and DIC simultaneously.